Apigenin protects from hepatorenal damage caused by lead acetate in rats. Issue 3 (22nd December 2022) - Fehaid, Alaa; Al‐Ghamdi, Mohammad S.; Alzahrani, Khalid J.; Theyab, Abdulrahman; Al‐Amer, Osama M.; Al‐Shehri, Saad S.; Algahtani, Mohammad; A. Oyouni, Atif Abdulwahab; Alnfiai, Mrim M.; Aly, Mohamed H.; Alsharif, Khalaf F.; Albrakati, Ashraf; et al.
Abstract: Exposure to lead (Pb) is associated with serious health problems including hepatorenal toxicity. Apigenin is a natural‐sourced flavonoid with promising antioxidant and anti‐inflammatory effects. In this research, we investigated the potential protective role of apigenin against lead acetate (PbAc)‐induced hepatorenal damage. Thus, this experiment studied the exposure of male Wistar Albino rats to apigenin and/or PbAc and their effects in comparison to the control rats. Apigenin administration decreased the levels of Pb and prevented the histopathological deformations in liver and kidney tissues following PbAc exposure. This was confirmed by the normalized levels of liver and kidney function markers. Additionally, apigenin inhibited significantly oxidative reactions through upregulating Nrf2 and HO‐1, and activating their downstreamed antioxidants accompanied by a marked depletion of pro‐oxidants. Moreover, apigenin decreased the elevated pro‐inflammatory cytokines and inhibited cell loss in liver and kidney tissues in response to PbAc intoxication in both tissues. The obtained results demonstrated that apigenin could be used to attenuate the molecular, biochemical, and histological alterations associated with Pb exposure due to its potent antioxidant, anti‐inflammatory, and antiapoptotic effects.